Role of infiltrating CD8 lymphocytes, microsatellite instability and h. pylori level in gastric cancer. - Leonardo, A (2018)
Modulation of immune system has demonstrated tumor response in Gastric Cancer. Tumor infiltrating lymphocytes and microsatellite instability are predictive biomarkers for response to anti-PD-L1 drugs in different malignancies, however, studies confirming it in gastric cancer are lacking. We evaluate the role of infiltrating CD8 lymphocytes over clinicopathological features including clinical stage, H. pylori presence, microsatellite instability and survival in Gastric Cancer.